PENYERAPAN LOGAM Pb DAN Cd OLEH ECENG GONDOK : PENGARUH KONSENTRASI LOGAM DAN LAMA WAKTU KONTAK - Nastiti Siswi Indrasti, , Suprihatin, Burhanudin dan Aida Novita (Department of Agroindustrial Technology, Bogor Agricultural University, 2006)
ABSTRACTThere have been many research on heavy metal removal using aquatic plant. This research was conducted using Eceng Gondok (Eichhornia crassipes) to absorb and accumulate Pb and Cd in a single mixed of them (Pb+Cd). Initial heavy metals concentrations used in this research were 0.5, 1.0, 3.0, 5.0 and 10.0 mg/l and contact period of 15 days. The result indicated that the rate of absorption and accumulation of mixed heavy metals (Pb+Cd) was higher compared to single heavy metal. The highest removal efficiencies for Pb (single), mixed (Pb+Cd) and Cd (single) were 88.10%, 86.06% and 85.83% respectively. Heavy metals were accumulated more in the root of Eichhornia crassipes than in the tissues (stem and leave). Heavy metals accumulation in the root for mixed (Pb +Cd), Pb (single) and Cd (single) were 21628 mg/kg, 16644 mg/kg, and 14057 mg/kg respectively, while heavy metals accumulation on plant tissues (stem and leaves) for mixed (Pb+Cd), Pb (single) and Cd (single) were 1305 mg/kg, 620.5 mg/kg, and 600.5 mg/kg. It is concluded that the higher the initial concentration of heavy metal in the waste water, the more metals can be absorbed by Eichhornia crassipes. The longer contact period, the more metals could be adsorbed too. Key words: Pb and Cd metals, consentration and contact period